Pelaksanaan Model Pembelajaran Inkuiri Pada Mata Pelajaran PAI - Zahiq, Moh; Hakim, Pauzi; Yanto, Ferry (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article describes the implementation of the inquiry model in Islamic Education subjects and identifies the supporting and inhibiting factors. To answer the above questions, the author conducted qualitative research by examining the perspectives of participants using multiple interactive strategies, such as direct observation, participant observation, in-depth interviews, and documentation. After analyzing the data obtained, the results showed that teachers were prepared, providing all learning tools before the lesson began, such as syllabi, curricula, lesson plans, evaluation materials, and other materials. The implementation of the inquiry learning model in PAI lessons influenced students' cognitive and scientific outcomes, especially for students who had more advanced thinking than other students. Even though students did not fully understand the material during the learning process, if the surrounding environment supported them, they would find it easy to apply what they had learned. The situation and conditions influenced the implementation of the inquiry learning model in Islamic Education.